Los principios configuradores del tipo social y la sociedad anónima en la Ley General de Sociedades, ¿una sociedad intuitu pecuniae? - Herrada Bazán, Víctor (Revista de Derecho, 2019)
From a dogmatic perspective, the public limited company is viewed as an intuitu pecuniaecorporate. Although this view is taken until today for most of the Peruvian doctrineand jurisprudence, a review of our corporate law allow us to discard that characterfrom this corporate type. This has major implications for the admissibility of certainconditions in statutes, not expressly provided in Peruvian law, insofar as that theyare not incompatible with its legal status. This paper defends the non-essentiality ofintuitu pecuniae characteristic of public limited companies, by treating about essentialelements of corporate forms in Peruvian law.
Keywords: Corporative types; public limited company; intuitu pecuniae; Corporative law; Peruvian law